Pembentukan Mikronukleus di Mukosa Bukal akibat Paparan Senyawa Kimia pada Berbagai Macam Pekerjaan - Setiabudi, Deny; Amalina, Rizki; Feranisa, Anggun (Universitas Sam Ratulangi, 2021)
Abstract: In general, an occupation could have hazzard and risk of exposure to genotoxic chemical compounds. These compounds could lead to micronucleus formation on buccal mucosa. This study was aimed to obtain the impact of chemical exposure on micronucleus formation in buccal mucosa at various occupations. This was a literature review study using databases of PubMed, ScienceDirect, and Google Scholar based on the keywords. The criteria of literatures were articles published in 2016-2021 using Indonesian or English language. The results showed that Â group compounds of polycyclic aromatic hydrocarbons (PAH), metals, carbamate, and organophospate, also compunds of silica, bezene, toluene, xylene (BTX), sevoflurane, desflurane, isoflurane, nitrous oxide, gemcitabin, and 5-fluoro uracil were genotoxic chemical compunds and could cause micronucleus formation in buccal mucosa of mechanics, grillers, miners, e-waste recyclers, construction workers, road markers, car painters, gasoline station workers, farmers, and healthcare workers. Genotoxic chemical compounds could be found excessively in occupational environment. These compounds could damage cellsâ€™ DNA and caused micronucleus formation on buccal mucosa of workers. It is suggested to study further about cell damage biomarkers caused by genotoxic chemical compound exposure.Keywords: micronucleus formation in buccal mucosa, chemical exposure of genotoxic compounds, occupational riskAbstrak: Suatu pekerjaan dapat memiliki risiko dan bahaya terpapar senyawa kimia yang bersifat genotoksik. Senyawa kimia tersebut dapat menyebabkan terbentuknya mikronukleus di mukosa pipi rongga mulut. Penelitian ini bertujuan untuk mengulas pengaruh paparan senyawa kimia pada berbagai macam pekerjaan terhadap pembentukan mikronukleus di mukosa bukal. Jenis penelitian ialah literature review. Penelusuran literatur melalui database PubMed, ScienceDirect, dan Google Scholar berdasarkan kata kunci yang sesuai. Kriteria literatur ialah terbitan tahun 2016-2021 dengan Bahasa Indonesia atau Inggris. Hasil penelitian mendapatkan senyawa kelompok polycyclic aromatic hydrocarbon (PAH), logam, carbamate, dan organophospate, serta senyawa silica, benzene, toluene, xylene (BTX), sevoflurane, desflurane, isoflurane, nitrous oksida, gemcitabin, dan 5-fluoro uracil merupakan senyawa kimia yang bersifat genotoksik dan dapat memicu pembentukan mikronukleus di mukosa bukal mekanik, pemanggang daging, penambang, pendaur ulang sampah elektronik, pekerja konstruksi, pekerja marka jalan, pengecat mobil, petugas SPBU, petani dan tenaga kesehatan. Senyawa kimia yang bersifat genotoksik banyak ditemukan di lingkungan pekerjaan. Senyawa tersebut dapat merusak DNA sel sehingga terbentuk mikronukleus di mukosa bukal pekerja. Disarankan untuk melakukan penelitian lanjut mengenai biomarker kerusakan sel akibat paparan senyawa kimia yang genotoksik.Kata kunci: pembentukan mikronukleus di mukosa pipi, paparan senyawa kimia genotoksik, risiko pekerjaan